Obrolan sebagai Obat Kesepian: Membangun Ikatan Baru antara Manusia dan Kecerdasan Buatan - Vandhika, Samuel; Sahrani, Riana (INSAN Jurnal Psikologi dan Kesehatan Mental, 2025)
The rise in the prevalence of loneliness is closely associated with the increasing utilization of artificial intelligence (AI) technologies, such as AI chatbot companionship (AICC), which are becoming increasingly employed by individuals experiencing loneliness. However, there is a lack of studies that attempt to address the psychological impact of using chatbots. The aim of this research is to investigate the correlation between the phenomenon of loneliness experienced by humans and the increased use of chatbot companionship through quantitative correlational analysis. The findings of the primary data analysis, which was based on research participants (n=237), suggest a significant relationship between loneliness and perceived use of AICC. The present finding highlights the importance of using AICC cautiously in early adulthood, as such technology may alleviate feelings of loneliness, overreliance has the potential to adversely impact the development of meaningful real-life social connections and relationships.